Knowledge, attitudes, and practices regarding type 2 diabetes and associated factors among rural adolescents in Indonesia: A cross-sectional study - Nila Kusumawati; Hanno Pijl; Halimatou Alaofè; Emul Yani; Desti Puswati; Abdul Hamid (PLoS ONE, 2026)
Introduction Type 2 diabetes (T2D) is an increasingly important public health concern in Indonesia and is increasingly affecting adolescents at a growing rate due to lifestyle transitions and limited awareness. Evidence regarding adolescents’ knowledge, attitudes, and practices (KAP) toward T2D in rural settings remains limited. This study assessed KAP levels related to T2D, identified sociodemographic factors associated with KAP outcomes, and examined interrelationships among KAP domains among rural Indonesian adolescents. Methods A cross-sectional study was conducted from September 2024 to February 2025 among 1,546 senior high school students in Kampar Regency, Riau Province. Participants were selected using multistage cluster sampling. Data were collected using a validated KAP questionnaire (Cronbach’s α = 0.725). Descriptive and inferential statistics, including Mann–Whitney U tests, Kruskal–Wallis tests, Spearman’s rank correlations, and multiple linear regression analyses, were used to examine KAP outcomes and associated factors. Results Participants demonstrated limited knowledge regarding T2D, particularly related to risk factors, symptoms, and complications. Although attitudes toward diabetes prevention were generally positive, preventive practices remained suboptimal, especially regarding physical activity. Female gender, peri-urban school location, higher academic rank, extracurricular participation, and prior exposure to diabetes information were associated with higher KAP scores. Knowledge was moderately associated with attitude but only weakly associated with preventive practices. Conclusions Rural adolescents demonstrated limited diabetes-related knowledge and suboptimal preventive behaviors despite generally positive attitudes toward T2D prevention. Several sociodemographic and school-related factors were associated with KAP outcomes. However, the weak relationship between knowledge and practice highlights a persistent gap between awareness and preventive behavior. School-based, peer-led, and after-school interventions that integrate education with behavioral reinforcement may strengthen diabetes prevention efforts among rural adolescents.